Inteligência artificial na educação: estudo com alunos e professores do curso de administração - Estumano, Roggério Oliveira (Brasil, 2024)
Artificial Intelligence (AI) represents an important technological innovation in the daily lives of people and organizations. One of the fields covered by this technology refers to the academic-pedagogical environment, with possibilities of use for students and teachers. This study analyzed the impact of AI in the university environment, focusing on the Administration course, in order to identify the main applications of students and teachers and understand the main opinions on this topic. To this end, descriptive research was carried out with a quantitative approach, using a closed online questionnaire, answered by students and teachers of the Administration course, at a Federal Education Institution, in Manaus/AM. The survey revealed that students used AI primarily to obtain feedback (58.5%) and assign tasks based on individual competence (50%), while teachers used it to improve teaching skills (47%) and provide learning strategies. adaptive teaching (47%). Students considered AI positive for academic performance (71%) and teachers considered AI positive for professional development (100%), although they expressed uncertainty about its socio-emotional implications. For the majority of students (67%) and teachers (79%), AI was not used appropriately ethically in the academic context. Furthermore, it was found that the Institution had little involvement with the use of AI tools for students and/or employees.